Korean Red Ginseng Enhances Neurogenesis in the Subventricular Zone of 1-Methyl-4-Phenyl-1,2,3,6-Tetrahydropyridine-Treated Mice - Ryu, Sun; Jeon, Hyongjun; Koo, Sungtae; Kim, Seungtae (Frontiers in Aging Neuroscience, 2018)
Regulation of adult neurogenesis plays an important role in therapeutic strategies for various neurodegenerative diseases. Recent studies have suggested that the enhancement of adult neurogenesis can be helpful in the treatment of Parkinson’s disease (PD). In this study, we investigated whether Korean red ginseng (KRG) can enhance neurogenesis in the subventricular zone (SVZ) of a PD mouse model. To accomplish this, male 8-week-old C57BL/6 mice were injected with vehicle or 20 mg/kg of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) four times at 2 h intervals. After the final injection, they were administered water or 100 mg/kg of KRG extract and injected intraperitoneally with 50 mg/kg of 5’-bromo-2’-deoxyuridine-monophosphate (BrdU) once a day for 14 consecutive days. After the last pole test, dopaminergic neuronal survival in the striatum and the substantia nigra (SN), cell proliferation in the SVZ and mRNA expression of neurotrophic factors and dopamine receptors in the striatum were evaluated. KRG administration suppressed dopaminergic neuronal death induced by MPTP in the striatum as well as the SN, augmented the number of BrdU- and BrdU/doublecortin (Dcx)-positive cells in the SVZ and enhanced the expression of proliferation cell nuclear antigen, brain derived neurotrophic factor (BDNF), glial cell derived neurotrophic factor (GDNF), cerebral dopamine neurotrophic factor (CDNF), ciliary neurotrophic factor (CNTF), dopamine receptor D3 (DRD3) and D5 mRNAs. These results suggest that KRG administration augments neurogenesis in the SVZ of the PD mouse model.